The impact of liberalization on higher education and domestic regulation - Tham, Siew Yean; Nik Mahmod, Nik Ahmad Kamal; Alavi, Rokiah (Springer, Singapore, 2018)
Tertiary education provided by private higher learning institutions (PHEIs) is one of the sectors that have been included in trade liberalization negotiations